Decision support based on single valued neutrosophic number for information system project selection - Silvia Liliana Tejada Yepez (Neutrosophic Sets and Systems, 2017)
Neutrosophic sets and its application to decision support have become a topic of great importance for researchers and practitioners alike. In this paper, a new model for decision making in the selection of information system projects is presented based on single valued neutrosophic number (SVN-numbers) allowing the use of linguistic variables with multiples points of view from experts.